2021
DOI: 10.12928/dpphj.v15i2.3992
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour of Health Faculty Students Responding to Hoaxes Related Covid-19 on Social Media

Abstract: Background: Hoax is still a problem in the era of information disclosure and technological advances currently. News or information containing hoax related to Covid-19 affects the handling effort of the Covid-19 pandemic. This research aimed to describe the behavior of health faculty students in responding to the hoaxes associated with Covid-19 on social media. Method: This research was a descriptive study. The sampling technique used was random sampling. The samples were 384 students who were required to compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Based on the findings, 28.1% of students still find it difficult to assess the quality and reliability of health information, and students with a limited level of digital health literacy will more often use social media to find health information [23]. In addition, health students also, when receiving health information, will have different responses there are 41.9% do not check the truth of health information because they feel that someone has reviewed it before [24]. These reasons illustrate how health students use digital health literacy skills.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings, 28.1% of students still find it difficult to assess the quality and reliability of health information, and students with a limited level of digital health literacy will more often use social media to find health information [23]. In addition, health students also, when receiving health information, will have different responses there are 41.9% do not check the truth of health information because they feel that someone has reviewed it before [24]. These reasons illustrate how health students use digital health literacy skills.…”
Section: Discussionmentioning
confidence: 99%
“…Based respondents, or 58% of the health faculty students studied, found that respondents received hoaxes related to COVID-19 through written and image forms [4]. Of the 15 health faculty students who had spread hoax news related to Covid-19, friends were the most targeted for spreading hoaxes, namely 13 respondents or 87% [5]. Another way that digital literacy competencies can do is to improve digital literacy skills.…”
Section: Introductionmentioning
confidence: 99%
“…Health faculty students are considered to have good knowledge and access to information on health issues [5]. Faculty of Health Science.…”
Section: Introductionmentioning
confidence: 99%